Amar, H. (2016). Pierre Bourdieu en el campo educativo argentino (1971-1989). Buenos Aires: Biblos. 139 pp. - Claudio Suasnabar (Revista Latinoamericana de Políticas y Administración de la Educación, 2017)
(-)